Analisa Kepuasan Layanan Perpustakaan dengan Minat Kunjung Mahasiswa di Perpustakaan STPKAT Santo Fransiskus Asisi Semarang Tahun 2023/2024 - Bersilius Candra Kusumawardi (JURNAL RISET MANAJEMEN (JURMA), 2025)
This study aims to determine whether there is a relationship between satisfaction with library services and students' interest in visiting the school library. The data analysis techniques used in this research include normality testing, linearity testing, reliability testing, and product-moment correlation testing. The research population consists of all 51 students of STPKAT Santo Fransiskus Asisi Semarang for the 2023/2024 academic year. The research subjects come from different educational levels and age groups, with varying abilities and interests in visiting the library. The sample consists of 10 students selected from those who have previously visited the school library, using a questionnaire as the research instrument. The data analysis techniques applied include normality testing, linearity testing, reliability testing, and product-moment correlation testing. The results of the product-moment correlation analysis show that the correlation value between the library service satisfaction variable (X) and students' interest in visiting the library is 0.667 > 0.05, indicating a significant relationship between these two variables.